Equal Education, Unequal Jobs: College and University Students with Disabilities - Stewart, Jennifer; Schwartz, Saul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2018)
Are students with a permanent disability more likely to drop out of post-secondary education than students without a permanent disability? Once they are out of postsecondary education, do their experiences in the labour market differ? Answers to these questions are necessary to evaluate current policies and to develop new policies.This paper addresses these two questions using a unique data set that combines administrative records from the Canada Student Loans Program with survey responses. Our measure of permanent disability is an objective one that requires a physician’s diagnosis. The survey data supply information on the students’ education and labour market status.Simple descriptive statistics suggest that, compared to students without a permanent disability, students with a permanent disability are equally likely to drop out of postsecondary education, but less likely to be in the labour force and more likely to be unemployed. We use propensity score matching to address potential selection into the group of students who documented their disability. The results using propensity score matching are consistent with the descriptive statistics.Our story is one of an underpublicized success—the rising number of students with disabilities in postsecondary institutions and their equal likelihood of graduation—and a persistent problem—the continued disadvantage that people with disabilities, even those with the same educational attainment as people without disabilities, face in the labour market.